Analysis of the Application of the Rest Hour Maritime Labor Convention 2006 on MV. Pan Energen Crews to Improve Working Conditions With Analytical Hierarchy Process (AHP) Method - Aprillia, Namira; Mulyatno, Imam Pujo; Mursid, Ocid; Yulianti, Serliana (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
The contribution made by the crew is very important for the welfare of the company and the performance on board. But their well-being has not been paid enough attention in the maritime world. Heavy workloads and working hours and lack of implementation of rest hours trigger human error and are prone to fatigue. The implementation of the Maritime Labor Convention 2006 has contributed significantly to the improvement of the working conditions of the crew.  The purpose of this study is to determine the right criteria and strategic solutions in helping to improve the application of rest hours to crew members. Criteria and strategy solutions were obtained through the Analytical Hierarchy Process (AHP) and Expert Choice methods are used as supporting software for calculations. The stages of observation, interviews, dissemination of questionnaires, modeling and choice are processes carried out in data processing.  Rest time criterias with a weight value of 0.534 and an inconsistency value of 0.004466 was the main criteria chosen by the respondents. Meanwhile, Sleep Duration is a strategy solution chosen as the top priority with the weight value of 0.220 with an inconsistency value of 0. The results of the two inconsistencies each have a CR value of < 0.1 indicating that the results of rest hour application data processing based on the 2006 Maritime Labor Convention can be declared consistent and accurate.